Effect of heating rates on the microstructure and gas permeation properties of carbon membranes - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail; K., Kadirgama; Mohamad Shahrizan, Moslan; Faten Ermala, Che Othman; Nor Hafiza, Ismail; Samykano, Mahendran; Zawati, Harun (Penerbit UTM Press, 2018)
High performance tubular carbon membrane (TCM’s) for CO2 separation were prepared by controlling the carbonization heating rates in range of 1-7 o C/min carbonized at 800 o C under Argon environment. A single permeation apparatus was used to determine the gas permeation properties of the membrane at room temperature. Fine turning of the carbonization condition was necessary to obtain the desired permeation properties. The preparation of PI/NCC-based TCM at low heating rate caused the gas permeance for the examined gas N2 and CO2 decreased whereas the selectivity of CO2/N2 increased. It was also identified that the gas permeation properties of the resultant TCM and its structure was highly affected by the heating rate. The best carbonization heating rate was found at 3o C/min for the fabrication of TCM derived via polymer blending of PI/NCC for CO2/N2 separation.